Research on Optimization Model of Crop Planting Strategy Based on Linear Programming - Cai, Zhidan; Chen, Wenjie; Chen, Xinyi (Transactions on Economics, Business and Management Research, 2024)
With the advancement of China's rural revitalization strategy, exploring scientific planting strategies is becoming increasingly important for achieving sustainable development of rural economy. This article takes a village in Huabei Mountain District as the research object and establishes a linear programming model to optimize the planting strategy of crops, to maximize the economic benefits of the village from 2024 to 2030. Firstly, based on the crop yield per mu, cost, and sales price data in 2023, a linear programming model was established with the goal of maximizing total revenue. Then, by analyzing the constraints of crop selection, continuous planting, legume crop rotation, and area allocation in the plot, the constraints of the objective function were defined. For the overproduction part, this article calculates the objective function under the conditions of unsold waste and 50% price reduction for sale. The results show that under the condition of unsold waste, the maximum total revenue of the village from 2024 to 2030 is approximately 2.38 million; under a 50% price reduction, the maximum total revenue for the village is approximately 2.59 million, and the provided planting plan meets all constraints.